2001
DOI: 10.1002/jmv.2042
|View full text |Cite
|
Sign up to set email alerts
|

Novel PCR assay for differential detection and screening of erythrovirus B19 and erythrovirus V9

Abstract: Diagnosis of erythrovirus B19 relies on serology and the detection of viral DNA. These techniques were believed to detect all field isolates because erythrovirus B19 has been known to undergo little genetic variation (1-2%). Recently, a distinct erythrovirus isolate termed V9, markedly different from erythrovirus B19 (>11% nucleotide disparity), was isolated from a child in France suffering from transient aplastic anemia. Standard PCR assays and serological tests failed to demonstrate an acute erythrovirus B19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 10 publications
3
51
1
Order By: Relevance
“…The geographical distribution of human erythrovirus genotypes is still largely unknown. The predominance of human erythrovirus genotype 1 in the United Kingdom is consistent with previous data; only a few genotype 2 and 3 variants have so far been identified in large-scale screening studies performed in Western countries (15,19,30,35). Until now, genotype 3 strains have occasionally been identified in France, where they have circulated as minority strains accounting for approximately 11% of the strains identified there between 1999 and 2001 (35).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The geographical distribution of human erythrovirus genotypes is still largely unknown. The predominance of human erythrovirus genotype 1 in the United Kingdom is consistent with previous data; only a few genotype 2 and 3 variants have so far been identified in large-scale screening studies performed in Western countries (15,19,30,35). Until now, genotype 3 strains have occasionally been identified in France, where they have circulated as minority strains accounting for approximately 11% of the strains identified there between 1999 and 2001 (35).…”
Section: Discussionsupporting
confidence: 90%
“…The prevalences observed were significantly higher than the 0.003 to 0.16% prevalences reported in previous studies (2,15,20,27,37,40,41). This discrepancy was clearly unrelated to sample origin but rather reflected differences in the sensitivity of the assays used in the different studies.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This method consisted of consensus primers for amplification of both strains, and two pairs of nested primers: one specific for the prototype and the other specific for the variant. Using this method 100 sera containing B19 immunoglobulin M and 50 blood-donor plasma pools were screened without detection of V9 (11). The same result came from 190 bone marrow samples of healthy subjects (10).…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference for B19 positivity between patients who received blood transfusion and who did not (p>0.05). Additionally, there are several studies which have reported values of 1/167-1/35,000 of B19 positivity in blood donors [18][19][20]. Although B19 infection is known to be transmitted via transfusion, it appears to be unrelated with transfusion; so studies including larger populations are needed to be performed as our study population was relatively small.…”
Section: Discussionmentioning
confidence: 95%